2019
DOI: 10.1111/jjns.12281
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ career identity, satisfaction with major, and career stress by career decision type

Abstract: Aim: This study aimed to understand the career decision types of nursing college students and accordingly identify their career identity, satisfaction with major, and career stress. Methods: Convenience sampling was used to recruit nursing students (N = 220) attending the same college in Korea. Data were collected from May 1 to May 30, 2017. General characteristics included sex, grade, religion, extracurricular activities, and motive for their nursing major choice. The instruments included career decision type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
2
15
0
4
Order By: Relevance
“…However, our findings suggest that the influence of a patriarchal cultural background can be overcome by demographic characteristics, motives for MS, and academic achievement. This is also supported by the results of previous studies [25][26][27], which showed that motive can affect MS. In these studies, MS was highest in students who voluntarily chose their majors based on suitability and interest.…”
Section: Discussionsupporting
confidence: 89%
“…However, our findings suggest that the influence of a patriarchal cultural background can be overcome by demographic characteristics, motives for MS, and academic achievement. This is also supported by the results of previous studies [25][26][27], which showed that motive can affect MS. In these studies, MS was highest in students who voluntarily chose their majors based on suitability and interest.…”
Section: Discussionsupporting
confidence: 89%
“…Professional identity is important for the education, career development, and retention of students [7,8]. The career identity of college students was found to be closely related to occupational decision-making [9,10]. Therefore, career identity for nursing students is important to produce nurses who can contribute positively to healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…The gap between the perceptions and the capability to work in a COVID-19 ward might impair nurses' competence, leading to identity crisis around continuing work or education even after the pandemic has receded. 26,27 Previous research suggests that emergency situations can elicit identity crises among nurses in the Japanese context. 28 In this study, nurses often cared for older people with multimorbidity, which needed close care and physical touch and felt identity crisis owing to a sense of inadequacy to conduct patient care.…”
Section: Discussionmentioning
confidence: 99%